2011
DOI: 10.1177/1470320310391334
|View full text |Cite
|
Sign up to set email alerts
|

Effects of renin-angiotensin system inhibition on right ventricular function in patients with mild essential hypertension

Abstract: RAS inhibition in patients with mild hypertension results in an improvement of RV global function which is unrelated to the reduction in blood pressure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 29 publications
2
7
0
Order By: Relevance
“…A history of hypertension was related to enhanced (more negative) RVLS, consistent with another study showing a positive correlation between systolic blood pressure and TAPSE . The higher LVEF among HF patients with hypertension may be explanatory, underscoring the nexus between LV and RV systolic function, but direct effects of antihypertensive drug therapy on RV function or confounding by hypotensive agents in HF patients with biventricular dysfunction are other possibilities.…”
Section: Discussionsupporting
confidence: 84%
“…A history of hypertension was related to enhanced (more negative) RVLS, consistent with another study showing a positive correlation between systolic blood pressure and TAPSE . The higher LVEF among HF patients with hypertension may be explanatory, underscoring the nexus between LV and RV systolic function, but direct effects of antihypertensive drug therapy on RV function or confounding by hypotensive agents in HF patients with biventricular dysfunction are other possibilities.…”
Section: Discussionsupporting
confidence: 84%
“…1 Modification of the RAAS through the use of RAAS inhibitors (RAASi), such as angiotensin-converting enzyme inhibitors (ACEIs), angiotensin receptor blockers (ARBs), and mineralocorticoid receptor antagonists (MRAs), is an important therapeutic option for the treatment of numerous cardiorenal conditions, reducing progression of chronic kidney disease (CKD), improving heart function and reducing cardiovascular morbidity and mortality. [2][3][4][5][6][7][8] However, RAASi use is known to reduce potassium (K + ) excretion and increase the risk of hyperkalemia in an already vulnerable population. 9,10 Hyperkalemia is a potentially life-threatening electrolyte imbalance, defined as a serum/plasma K + level above the normal physiological range of 3.5 to 5.0 mmol/L, 11 that can induce electrophysiological disturbances, potentially leading to cardiac arrhythmias, cardiac arrest, and sudden death.…”
mentioning
confidence: 99%
“…20 Several studies have consistently demonstrated that aldosterone antagonism is able to rescue adverse RV geometry and dysfunction. 21 In our study, RV function was assessed by using TDI, which has recently emerged as a powerful diagnostic tool in detecting early abnormalities of cardiac function. 22 Specifically, TDI MPI is one of the most reliable indices of ventricular performance, because it includes parameters relative to both cardiac contraction and relaxation (IVRT þ IVCT/ET).…”
Section: Discussionmentioning
confidence: 99%